How effective are rewards programs in promoting payment card usage? Empirical evidence - Santiago Carbó-Valverde; José M. Li\~nares-Zegarra (European Central Bank (ECB), 2009)
Card issuers have mainly relied on rewards programs as their main strategic driver to increase electronic payments. However, there is scarce evidence on the effectiveness of rewards programs. This paper offers novel evidence on two key issues: i) it measures the impact of rewards programs on the use of payment cards; and ii) it quantifies their economic impact in terms of the cash substitution. The results show that rewards may significantly modify preferences for card payments, their economic impact vary significantly across types of rewards and merchant activities and rewards seem to be more effective on average for debit cardholders.
Keywords: G20; D12; E41; 330; cardholders; merchants; payment cards; preferences; rewards; Kreditkarte; Elektronisches Geld; Beziehungsmarketing; Konsumentenverhalten; Rationalität